Effects of Family Empowerment on Increasing Family Support in Patients with Type-2 Diabetes Mellitus - Luthfa, Iskim; Ardian, Iwan (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: Patients with type-2 Diabetes Mellitus (DM) need support from their families to perform self-care to prevent complications; however, not all families have effective support. Family empowerment is a family-based strategic intervention which can improve family support to those patients.Purpose: This study aimed to determine the effects of family empowerment on increasing family support in patients with type 2 DM.Methods: This study used a quasi-experiment with non-equivalent control group design. Forty-six respondents were recruited using a consecutive sampling technique and assigned to the control and intervention groups. Respondents in the intervention group were given family empowerment intervention by visiting their homes four times, for 120 minutes each. In contrast, the control group was given the intervention of standard booklets. The Hensarling Diabetes Family Support Scale (HDFSS) was used to observe the family support on both groups. Data were analyzed by independent t-test.Results: Results showed that there was a significant difference between the intervention and the control group with t=7.86 and p-value of 0.00. There were mean differences of 2.29 and 0.28 between the intervention and the control group, respectively.Conclusion: Family empowerment affected family support in patients with type-2 DM. Based on this study, it is recommended that the health workers advocate and encourage the family in the planning management of patients with diabetes mellitus.